Analysis of the Influence of the Parameters of the Pendulum Mechanism of the Swashplate Engine on the Dynamic Performance - Deng Tao; Zheng Yuwei; Zhang Yuxiao; Liu Ping (Jixie chuandong)
In order to study the influence of relevant parameters of the swashplate engine pendulum mechanism on engine dynamic performance, a mathematical model which can express the relationship between its design parameters and engine dynamic performance is established through the derivation of relevant parameters of the swashplate engine pendulum mechanism. Combined with the mathematical model, the influence of the change of the number of cylinders of the pendulum mechanism on the output speed and the displacement of the center of mass of the swashplate are studied using the control variable method, and the Admas simulation analysis is carried out. The results show that when the number of cylinders is selected as the independent variable, the inclination angle of the swashplate decreases gradually from 29.93° to 14.26°, and the average deviation of speed is the smallest when the number of cylinders is 7, which is 0.005 4 r/min; the average displacement of the swashplate centroid on x-axis and y-axis is also the smallest, which are -0.005 9 mm and -0.016 7 mm respectively; the average displacement on the z-axis is 0.038 8 mm, which is not the minimum value, but the offset amplitude is smaller. The results show that when the number of engine cylinders is 7 and the inclined angle of the swashplate is 16.35°, the stability of the spindle speed and the stability of swashplate are the best, which provides some reference for the parameter design of swashplate engines.